Предмет: Алгебра,
автор: Hello5674
Решите пожалуйста!
У простите выражение
4с•(с-2)-(с-4)^2
3а•(а+2)-(а+3)^2
3•(у-1)^2+6у
8с+4•(1-с)^2
Ответы
Автор ответа:
0
4с•(с-2)-(с-4)^2=4c^2-8c-(c^2-8c+16)=4c^2-8c-c^2+8c-16=3c^2-16
3а•(а+2)-(а+3)^2=3a^2+6a-(a^2+6a+9)=3a^2+6a-a^2-6a-9=2a^2-9
3•(у-1)^2+6у=3*(y^2-2y+1)+6y=3y^2-6y+3-6y=3*(y^2+1)
8с+4•(1-с)^2=8c+4*(1-2c+c^2)=8c+4-8c+4c^2=4*(c^2+1)
3а•(а+2)-(а+3)^2=3a^2+6a-(a^2+6a+9)=3a^2+6a-a^2-6a-9=2a^2-9
3•(у-1)^2+6у=3*(y^2-2y+1)+6y=3y^2-6y+3-6y=3*(y^2+1)
8с+4•(1-с)^2=8c+4*(1-2c+c^2)=8c+4-8c+4c^2=4*(c^2+1)
Похожие вопросы
Предмет: Геометрия,
автор: ulanaevstratova3
Предмет: Математика,
автор: hloyaburzhua
Предмет: Қазақ тiлi,
автор: iouh
Предмет: Химия,
автор: iliz
Предмет: Алгебра,
автор: eseniz